2021
DOI: 10.1186/s13073-021-00840-y
|View full text |Cite
|
Sign up to set email alerts
|

Guild-based analysis for understanding gut microbiome in human health and diseases

Abstract: To demonstrate the causative role of gut microbiome in human health and diseases, we first need to identify, via next-generation sequencing, potentially important functional members associated with specific health outcomes and disease phenotypes. However, due to the strain-level genetic complexity of the gut microbiota, microbiome datasets are highly dimensional and highly sparse in nature, making it challenging to identify putative causative agents of a particular disease phenotype. Members of an ecosystem se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 96 publications
0
106
0
Order By: Relevance
“…Microbes that likely work together to contribute to the same ecological function could be identified by clustering co-abundance groups (CAGs) based on their co-variation of abundance ( Wu et al, 2021 ). We constructed CAGs of the gut microbiota in experimental sows.…”
Section: Methodsmentioning
confidence: 99%
“…Microbes that likely work together to contribute to the same ecological function could be identified by clustering co-abundance groups (CAGs) based on their co-variation of abundance ( Wu et al, 2021 ). We constructed CAGs of the gut microbiota in experimental sows.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have introduced the concept of a ‘guild’ into the study of the gut microbiota, defining a group of microorganisms that utilize similar resources or perform the same biological function as the same guild to identify potential clusters associated with specific disease phenotypes and identify candidate gut microbes that may contribute to human health and disease[ 37 ]. Using a clinical study of genetically obese children, the researchers found that the abundance of one strain of E. coli increased sharply after 30 d of eating a diet rich in nondigested carbohydrates, while the abundance levels of the other four strains decreased[ 37 ]. Therefore, guilds, as an important form of intermember organization in ecology, can better reflect the changes in specific responses of strains.…”
Section: Association Of the Gut Microbiota With Obesitymentioning
confidence: 99%
“…The notion of eco-group (or guild), i.e., a set of bacterial taxa that perform similar functions, is very useful to understand microbial ecology [45, 46]. We divided the entire gut microbiota into three eco-groups: (1) 5 primary degraders of inulin; (2) 32 generic responders to inulin intervention; (3) non-responders.…”
Section: Resultsmentioning
confidence: 99%